An Evaluation of Acute and Subchronic Toxicities of a Nigerian Polyherbal Tea Remedy - Ogbonnia, Steve O.; Mbaka, Godwin O.; Anyika, Emmanuel N.; Emordi, Jonathan E.; Nwakakwa, Ndubuisi; Nwakakwa, Ndubuisi (Pakistan Journal of Nutrition, 2011)
The evaluation of the acute and subchronc toxicities of a Nigerian polyherbal tea remedy, prepared with Anthocleista vogelii, Ficus exasperata leaves and Viscum album (mistletoe), was carried out in Swiss albino mice and Wistar rats of both sexes. The lyophilized extract in the dose ranges of 1.0 g to 20.0 g/kg body weight was administered orally to the mice and observed continuously for the first 4 h and hourly for the next 12 h, then 6 hourly for 56 h (72 h, acute toxicity). Wistar rats were also fed with different doses of the lyophilized formulation for 30 days and the effects on some tissues - heart, liver and testes - were histologically evaluated. Also the effects on the biochemical and haematological parameters were evaluated (subchronic toxicity model). The median acute toxicity value (LD50) of the polyherbal tea was determined to be 8.970 g/kg body weight. The tea significantly reduced (p<0.05) plasma glucose and Low Density Lipoprotein (LDL)-cholesterol levels, but increased High Density Lipoprotein (HDL)-cholesterol in the treated groups compared to the control. No significant increase in the body weight was observed in the treated groups. Aspartate Aminotransferases (AST) and creatinine levels were not significantly increased while significant decrease in Alanine Aminotransferases (ALT) levels were observed in all the treated groups. The high LD50 value of the drug implies that the drug could be safe in one dose treatment. The study also revealed that the polyherbal tea may have good hypoglycemic effects and favourable reducing effects on the cardiovascular risk factors.